2018
DOI: 10.1209/0295-5075/123/14004
|View full text |Cite
|
Sign up to set email alerts
|

Forced flow of granular media: Breakdown of the Beverloo scaling

Abstract: The Beverloo scaling for the gravity flow of granular materials through orifices has two distinct universal features. On the one hand, the flow rate is independent of the height of the granular column. On the other hand, less well-known yet more striking, the flow rate is fairly insensitive to the material properties of the grains (density, Young's modulus, friction coefficient, etc.). We show that both universal features are lost if work is done on the system at a high rate. In contrast to viscous fluids, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…In fact, materials of diverse nature, such as cereals, drugs, or minerals, are stored in granular form and have to be processed accordingly. Even so, given the complexity of discrete media, the silo discharge continues to be an open problem from the point of view of its underlying physics and is, indeed, a topic under very active research [3][4][5][6][7]. The most widely accepted expression to predict the mass flow rate W of granular matter in a silo was proposed by Beverloo et al [8] in 1961,…”
Section: Introductionmentioning
confidence: 99%
“…In fact, materials of diverse nature, such as cereals, drugs, or minerals, are stored in granular form and have to be processed accordingly. Even so, given the complexity of discrete media, the silo discharge continues to be an open problem from the point of view of its underlying physics and is, indeed, a topic under very active research [3][4][5][6][7]. The most widely accepted expression to predict the mass flow rate W of granular matter in a silo was proposed by Beverloo et al [8] in 1961,…”
Section: Introductionmentioning
confidence: 99%
“…A discussion on the relation between pressure, flow rate and dissipated power can be found in Ref. [18]. In this paper we focus only on velocity profiles and leave the discussion on pressure profiles for a future work.…”
Section: Flow Rate and Bottom Pressurementioning
confidence: 99%
“…Recently, it has been shown that the use of an overweight on top of the granular column of a discharging silo induces an increase of the flow at the final stages of the discharge [18]. This is once again in contrast to viscous fluids since these decrease their flow rate during discharge from a tank even if a constant overpressure is applied to the free surface.…”
mentioning
confidence: 99%
See 2 more Smart Citations